Increase in Bcl2 expression of penile and prostate cells of Sprague Dawley male rats following treatment with buceng (combination of Pimpinella alpina molk with Eurycoma longifolia Jack) (Medical Journal of Indonesia, 2015)
Background: Treatment with buceng combination of Eurycoma longifolia Jack and Pimpinella alpine Molk has been proven to increase testosterone level, decrease apoptosis and caspase3 expression. Bcl2 is an antiapoptotic protein found in cytoplasm which inhibits cells apoptosis. This study was aimed to investigate the effect of buceng on Bcl2 expression on penile and prostate tissues of the rats. Methods: In this experimental study, 24 male Sprague Dawley rats of 90 days old, weighing ± 300 grams, were randomly assigned into four groups. Group A, normal rats. Group B, castrated rats and treated with buceng 100 mg/day, per oral (Cast-Bcg); Group C, castrated rats and treated with 2 ml of water as placebo against buceng (Cast-Plac). Group D, castrated rats, treated with mesterolone 6.75 mg/day, per oral, as exogenous testosterone (Cast-Mest). All rats were treated for 30 days. Manova test was used to analyze the different expression of Bcl2 among groups with significance level at p ≤ 0.05. Results: Castration was associated with significant decrease of Bcl2 expression in the penile and prostate tissues (53.0 and 50.9%, respectively) compared to normal rats (82.6 and 84.2%, respectively, p < 0.001). Treatment with mesterolone reversed Bcl2 expression (77.1 and 78.1%) to a near normal level. The same level of Bcl2 expression was also observed with buceng treatment (73.8 and 78.2%). Conclusion: The treatment with buceng could enhance Bcl2 expression in penile and prostate tissues, comparable to normal rats and mesterolone treated rats.